2019
DOI: 10.1371/journal.pone.0211898
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA methylation of peripheral blood leukocytes from dogs bearing multicentric non-Hodgkin lymphomas and healthy dogs: A comparative study

Abstract: Non-Hodgkin lymphomas are among the most common types of tumors in dogs, and they are currently accepted as comparative models of the disease in humans. Aberrant patterns of DNA methylation seem to play a key role in the development of hematopoietic neoplasms in humans, constitute a special mechanism of transcriptional control, and may be influenced by genetic and environmental factors. Blood leukocyte DNA global methylation has been poorly investigated in dogs. The aim of this study is to examine whether peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 79 publications
0
10
1
Order By: Relevance
“…Having male DNAme as a control and an upper threshold for calling genes as subject to XCI should reduce the chance of calling a gene as subject to XCI if it is instead silenced on both copies of the X in a tissue-specific manner. For the primate and dog samples which used the human 450k DNAme array, only probes which mapped consistently between the species were kept by the source publications [ 50 , 51 ], and so these species may be enriched for genes with a conserved XCI status. Utilizing datasets from different studies confounds the species differences with other experimental differences including sample size as well as inclusion of male samples.…”
Section: Discussionmentioning
confidence: 99%
“…Having male DNAme as a control and an upper threshold for calling genes as subject to XCI should reduce the chance of calling a gene as subject to XCI if it is instead silenced on both copies of the X in a tissue-specific manner. For the primate and dog samples which used the human 450k DNAme array, only probes which mapped consistently between the species were kept by the source publications [ 50 , 51 ], and so these species may be enriched for genes with a conserved XCI status. Utilizing datasets from different studies confounds the species differences with other experimental differences including sample size as well as inclusion of male samples.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies of XCI status calls using DNAme in human did not see many differences in DNAme-based XCI status across tissues [23], so different tissues analyzed may not cause many discordancies. For the primate and dog samples which used the human 450k methylation array, only probes which mapped consistently between the species were kept by the source publications [50,51], and so these species may be enriched for genes with a conserved XCI status. Utilizing datasets from different studies confounds the species differences with other experimental differences including sample size as well as inclusion of male samples.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that genome-wide hypomethylation was frequently found in grade III canine mast cell tumor, which is the most common skin tumor in dogs, thus correlating DNA hypomethylation with the aggressiveness of this type of cancer (53). In addition, dogs bearing non-Hodgkin lymphoma (NHL) exhibit higher DNA global hypomethylation of circulating leukocytes in comparison with healthy dogs (54). DNA hypomethylation was also observed in canine lung cancer samples and in metastatic osteosarcoma from the primary lung cancer (55).…”
Section: Dna Methylation and Canine Cancermentioning
confidence: 99%